Psychological Well-Being of High School Students During the Pandemic: Kesejahteraan Psikologis Siswa SMA Dimasa Pandemi - Fahmawati , Zaki Nur; Laili, Nurfi; Paryontri , Ramon Ananda (Universitas Muhammadiyah Sidoarjo, 2022)
The COVID-19 pandemic has had an impact on various groups, including high school students. Changes in various aspects of life can have a negative effect on the quality of life of high school students. Naturally, high school students are in their teens, which is a period of crisis as they experience changes, both physically and psychologically. Adolescents who fail to manage changes in themselves and adjust to various changes during this pandemic can fall into negative tendencies. Psychological well-being is an important factor that can help high school students in dealing with times of crisis and turmoil and various changes during the pandemic. The purpose of this study was to describe the psychological well-being of high school students during pandemic. This study uses a quantitative descriptive method. The research subjects were 273 teenagers at SMA Negeri 3 Sidoarjo. The sample was determined by the cluster sampling method. Meanwhile, data were collected using a psychological well-being scale from Caroll D.Ryff. The results showed that most of the students of SMA Negeri 3 Sidoarjo had psychological well-being in the moderate category. The most influential dimension on students' psychological well-being is personal growth, where adolescents feel happy when they are able to develop their potential.